Technology and Human Agency in Kurt Vonnegut’s Harrison Bergeron and Player Piano - Zarei , Erfan; Safari Monfared, Mahdi (International Journal of Language and Literary Studies, 2023)
The present study aims to explore the intricate relationship between technology and ideology in the formation of social structures. It highlights the increasing dependence on super-advanced technology and touches upon the potential dangers associated with its manipulative use. Furthermore, this study examines the dehumanizing effects of technology highlighting how it can serve as a tool for not only imposing ideology but also eroding a character’s agency. Drawing on Slavoj Zizek’s theories regarding technology and agency, the profound impact of technology and ideology on human agency is addressed. To illustrate the effects of technology on society and government control, Kurt Vonnegut’s short story, "Harrison Bergeron," and the novel Player Piano are analyzed. In Vonnegut’s dystopian stories, the government uses technological devices to enforce ideology and manipulate characters even leading to job unemployment. Ultimately, the article achieves its three-fold objectives by examining how ideological subjects regard their unfreedom as freedom, examining the dehumanizing effects of technology as a means of ideological enforcement, and analyzing the erosion of agency of ideological subjects in a technologically advanced society governed by an oppressive regime such as the one in Harrison Bergeron and the elites in Player Piano.